Clinical features of adult patients with avoidant/restrictive food intake disorder presenting for medical stabilization: A descriptive study. Issue 5 (25th January 2023) - Nitsch, Allison; Watters, Ashlie; Manwaring, Jamie; Bauschka, Maryrose; Hebert, Melanie; Mehler, Philip S.
Abstract: Objective: The purpose of this study is to describe the clinical features of adult patients with avoidant/restrictive food intake disorder (ARFID) to better understand the medical findings, psychological comorbidities, and laboratory abnormalities in this population. Method: We completed a retrospective chart review of all adult patients with a diagnosis of ARFID, admitted for medical stabilization, between April 2016 and June 2021, to an inpatient hospital unit, which specializes in severe eating disorders. Information collected included anthropomorphic data, laboratory assessments, and medical history at time of admission. Results: One hundred and twenty‐two adult patients with ARFID were identified as meeting inclusion criteria for the study. The most common ARFID presentation was "fear of adverse consequences." The majority were female (70%), with an average age of 32.7 ± 13.7 years and mean percent of ideal body weight (m%IBW) of 68.2 ± 10.9. The most common laboratory abnormalities were low serum prealbumin and vitamin D, hypokalemia, leukopenia, and elevated serum bicarbonate. The most common psychiatric diagnoses were anxiety and depressive disorders, and the most common medical diagnoses were disorders of gut–brain interaction (DGBI). Discussion: This is the largest study to the authors' knowledge of medical presentations in adult patients with ARFID. Our results reflect that the adult patient with ARFID may, in some aspects, present differently than pediatric and adolescent patients with ARFID, or from ARFID patients requiring less intensive care. This study highlights the need for further investigation of adult patients with ARFID. Public Significance: ARFID is a restrictive eating disorder first defined in 2013. This study explores the medical presentations of adult patients (>18 years old) with ARFID presenting for specialized eating disorder treatment and identifies unique features of the adult presentation for treatment, compared to pediatric and adolescent peers.